TIPOLOGI KITAB RIYADLUSH SHALIHIN DALAM KODIFIKASI HADIS - Kurdian, Nur Kholis (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2013)
Hadith Â is Â one Â of Â the Â two Â sources Â of Â Islam, Â both Â are Â revelation Â from Allah Â Almighty Â can Â not Â be Â separated, Â so Â that Â the Â scholars Â since Â the Â time of Â the Â companions Â of Â the Â Prophet Â to Â the Â generations Â after Â giving Â great attention Â to Â them, Â they Â collect Â the Â hadith Â of Â the Â Prophet Â either Â in Â the Â form of writing Â and memorization or Â teach it Â to later generations. Collection Â of Â hadiths Â are Â then Â collected Â into Â books Â of Â hadith Â with Â a variety Â of Â shades, Â such Â as Â Musnad Â books, Â jawami', Â Sunan, Â mukhtalif Â hadith, Â ajza' Â , Â Mustadrak, Â muâ??jam, Â mustakhraj, Â al-jam'u Â baina Â alshahihain, Â al-maudlu'at, Â al-ahkam, Â gharib Â al-hadith, Â al-targhib Â wa Â altarhib, athraf, takhrij, zawaid and others. This Â paper Â discusses Â the Â book Â of Â Riyadh Â al-Saliheen Â which Â is Â one hadith Â books Â are Â well Â known Â in Â the Â Islamic Â world. Â The Â author Â will discuss Â it Â into Â 2 Â parts. Â First: Â a Â discussion Â of Â hadith Â book Â style Â category Â of Riyadh Â al-Saliheen. Â Second, Â the Â discussion Â time Â appeared Â shades Â hadith books of Â Riyadh al-Saliheen . This Â paper Â discusses Â some Â of Â the Â issues Â related Â to Â the Â typology Â and the Â codification Â of Â hadith Â and Â scope Â of Â Riyadh Â al-Saliheen Â book. Â The authors Â claimed Â that Â the Â book Â of Â Riyadh Â al-Saliheen Â is Â one Â of Â the Â books of Â hadith Â al-targhib Â wa Â al-tarhib Â the Â best Â , Â and Â the Â emergence Â of Â this hadith Â book Â style Â since Â the Â second Â century Â hijriyah Â as Â thematic Â work, then the Â peak Â is in the sixth century to the Â ninth century.